Cu(ATSM) Increases P-Glycoprotein Expression and Function at the Blood-Brain Barrier in C57BL6/J Mice - Jae Pyun; HuiJing Koay; Pranav Runwal; Celeste Mawal; Ashley I. Bush; Yijun Pan; Paul S. Donnelly; Jennifer L. Short; Joseph A. Nicolazzo (MDPI AG, 2023)
P-glycoprotein (P-gp), expressed at the blood-brain barrier (BBB), is critical in preventing brain access to substrate drugs and effluxing amyloid beta (Aβ), a contributor to Alzheimer's disease (AD). Strategies to regulate P-gp expression therefore may impact central nervous system (CNS) drug delivery and brain Aβ levels. As we have demonstrated that the copper complex copper diacetyl bis(4-methyl-3-thiosemicarbazone) (Cu(ATSM)) increases P-gp expression and function in human brain endothelial cells, the present study assessed the impact of Cu(ATSM) on expression and function of P-gp in mouse brain endothelial cells (mBECs) and capillaries in vivo, as well as in peripheral organs. Isolated mBECs treated with Cu(ATSM) (100 nM for 24 h) exhibited a 1.6-fold increase in P-gp expression and a 20% reduction in accumulation of the P-gp substrate rhodamine 123. Oral administration of Cu(ATSM) (30 mg/kg/day) for 28 days led to a 1.5 & 1.3-fold increase in brain microvascular and hepatic expression of P-gp, respectively, and a 20% reduction in BBB transport of [3H]-digoxin. A metallomic analysis showed a 3.5 and 19.9-fold increase in Cu levels in brain microvessels and livers of Cu(ATSM)-treated mice. Our findings demonstrate that Cu(ATSM) increases P-gp expression and function at the BBB in vivo, with implications for CNS drug delivery and clearance of Aβ in AD.